THE LIMITS TO THE WORK OF UNDERCOVER INVESTIGATORS, AS SET OUT IN THE ECTHR CASE-LAW - Elena ANGHEL (Challenges of the Knowledge Society, 2025)
According to art. (4) and (5) CPP, undercover investigators are operational workers of the criminal investigation police, whose role is to collect data and information and make it available in full to the prosecutor conducting or supervising the criminal prosecution, by drawing up a report. The work of the undercover investigator must be carried out under the observance of the fair trial guarantees. However, as this study will demonstrate, the ECtHR judgments reveal a practice that is at least surprising: not infrequently, criminal activity has been provoked by prosecuting authorities in order to gather the evidence necessary to bring a case to trial. Art. 148 para. (7) CPP provides that judicial bodies may use or make available to the undercover investigator any documentary evidence or objects necessary for the conduct of the authorized activity. The activity of the person making available or using the documentary evidence or objects does not constitute an offense. Notwithstanding, in practice, the judicial bodies have assigned to the wording of art. 148 para. (7) CPP the interpretation according to which, in the exercise of their legal powers, they may draw up/enact/issue any documentary evidence or objects necessary for the performance of the authorized activity, giving them an appearance of legality, with the purpose of provoking the commission of a crime. In this background, by examining the ECtHR case-law on the use of special investigative techniques, we note that the Court of Strasbourg has repeatedly held that the Romanian State violated the general principles of fair trial guarantees, on the grounds that the criminal activity was provoked by the criminal prosecution authorities.